Deterrent Effect and Human Rights: A Critical Analysis of Chemical Castration Implementation in Child Protection Law - Arie Purnomo; Desvika Rizqi Karyma; Syahrani Kurniati; Tansah Hanggawa Mukti; Muhammad Daffa Eka Rawie (Jurnal Dinamika Hukum, 2025)
Sexual violence against children is an extraordinary crime that demands firm legal enforcement to ensure both deterrence and protection for victims. To address this issue, the Indonesian government introduced chemical castration through Government Regulation in Lieu of Lieu of Law (Perppu) Number 1 of 2016 as an additional sanction for perpetrators of sexual violence against children. This study critically examines the implementation of chemical castration in Indonesia by highlighting the legal framework and the tension between deterrence and the protection of human rights. The analysis draws on relevant legislation, criminal law concepts, and selected court decisions to evaluate the policy’s practical and ethical challenges. The findings reveal that chemical castration has not been an effective deterrent due to the absence of technical implementation guidelines and objections from medical professionals, particularly the Indonesian Medical Association (IDI), based on professional ethics. These obstacles have weakened both deterrence and rehabilitation efforts, creating ethical and legal dilemmas in their enforcement. Therefore, a policy reformulation is necessary by positioning chemical castration within a double-track system that integrates punishment and rehabilitation to achieve a balanced approach between deterrence, offender recovery, and human rights protection. Future implementation should be supported by clear procedural standards, inter-agency coordination, and ethical oversight to ensure that the policy aligns with the principles of justice and human dignity.